The Biodiversity richness of the Macedonian Snake Fauna (Reptilia: Serpentes) - Petkovski, Svetozar; Sidorovska, Vesna; Dzukic, Georg (Macedonian Journal of Ecology and Environment, 2001)
The Balkan Whip Snake Coluber gemonensis (Laurenti, 1768), has been found in the vicinity of Debar, Southeastern Macedonia. It is the first record of this species in the Republic of Macedonia. Including this record, the total number of snake species known to exist within the Republic of Macedonia is now 16. Keeping in mind that the total number of the snake species reported from the Balkan Peninsula is 21 (including the Greek islands), then the Macedonian snake fauna encompasses 76% of the Balkan snake species. The Pleistocene glaciations have had the most significant impact (i.e., they determined the composition of the snake fauna in the various biomes of the whole Cholarctic, especially in the Balkans). Consequently, the most striking feature of the recent Macedonian snake fauna is its great heterogeneity.